2021
DOI: 10.1038/s41416-021-01555-y
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of breast cancer patients’ satisfaction and experience with oncology telemedicine visits during the COVID-19 pandemic

Abstract: s Introduction During the COVID-19 pandemic, teleconsultation was implemented in clinical practice to limit patient exposure to COVID-19 while monitoring their treatment and follow-up. We sought to examine the satisfaction of patients with breast cancer (BC) who underwent teleconsultations during this period. Methods Eighteen centres in France and Italy invited patients with BC who had at least one teleconsultation during the first wave of the COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
2
46
0
2
Order By: Relevance
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study in [ 40 ] reported the evolution of a multidisciplinary center for myocarditis towards a telemedicine system. Important applications are recorded in oncology, such as in breast cancer [ 21 ], lung cancer [ 25 ], connections to the stoma centers [ 29 ], the management of patients with differentiated thyroid cancer [ 39 ], and related radiotherapy applications [ 35 ]. The neurology sector has also recorded an important use of applications in Parkinson’s disease [ 44 ]; in the use of telemedicine for the multidisciplinary assessment of patients with Amyotrophic Lateral Sclerosis [ 47 ]; for multiple sclerosis [ 28 ]; for a headache specialist center; and in applications of telephysiotherapy [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 82% ( n = 2207) patients indicated overall satisfaction with virtualized care [ 29 ]. A study in France and Italy among 1244 breast cancer patients showed high levels of approval for telehealth visits during the COVID-19 pandemic [ 32 ]. Overall, our findings underline the relevance and support further acceptance of the implementation of telehealth as part of comprehensive cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients receiving radiation, most were satisfied with virtual postradiation visits, and nearly 90% of patients in 1 study preferred to keep telehealth as part of their care 40,41 . Numerous studies reported positive patient perceptions of virtual visits, and patients frequently highlighted reduced travel time and increased convenience as the biggest positives 2,26,41–47 . One study estimated that virtual visits saved 20,000 miles of travel, more than 200 miles per patient 42 .…”
Section: Virtual Care In Oncologymentioning
confidence: 99%